Writing Errors: A Study of Students Linguistic Errors in Insya Muwajjah Learning - Noza Aflisia; Kasmantoni; Yunika Febri Yanti (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This research aims to analyze students' linguistic errors when learning insya muwajjah. This research is a case study of students from the Arabic Education Study Program at IAIN Curup using a qualitative approach. The primary data source comes from 11 fourth-semester students and Insya Muwajjah, the subject lecturer. Meanwhile, secondary data comes from student essays in the Insya Muwajjah subject. Apart from that, it also uses books and articles from scientific journals. Data collection instruments are interviews, surveys, and documentation. Data analysis methods include condensation, display, and conclusion drawing/verification. The research results show that students' linguistic errors in Insya Muwajjah learning include four errors. First, phonetics, namely, students cannot differentiate between letters that have similar sounds. Second, morphological, namely, students do not understand word changes. Third, syntax, namely, students' lack of grammar understanding, so there are still many errors in the final lines of words. Fourth, semantics: many students still use inappropriate words in sentences.